2017
DOI: 10.3390/genes8120356
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Proteins in Wheat Cultivars with Contrasting Nitrogen Efficiencies under the Combined Stress of High Temperature and Low Nitrogen

Abstract: Productivity of wheat (Triticum aestivum) is markedly affected by high temperature and nitrogen deficiency. Identifying the functional proteins produced in response to these multiple stresses acting in a coordinated manner can help in developing tolerance in the crop. In this study, two wheat cultivars with contrasting nitrogen efficiencies (N-efficient VL616 and N-inefficient UP2382) were grown in control conditions, and under a combined stress of high temperature (32 °C) and low nitrogen (4 mM), and their le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 81 publications
4
12
0
Order By: Relevance
“…Our integrated model overcomes this and not only suggests the changes in mRNA levels and how these affect photosynthetic metabolism, but was able to predict the acclimation of photosynthetic CO 2 assimilation that had been observed (Figure 1). Previous studies have reported proteome-level changes in response to elevated CO 2 in soybean and other crop species (Ainsworth and Long, 2005, Bokhari et al, 2007, Taub et al, 2007, Yousuf et al, 2017, Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our integrated model overcomes this and not only suggests the changes in mRNA levels and how these affect photosynthetic metabolism, but was able to predict the acclimation of photosynthetic CO 2 assimilation that had been observed (Figure 1). Previous studies have reported proteome-level changes in response to elevated CO 2 in soybean and other crop species (Ainsworth and Long, 2005, Bokhari et al, 2007, Taub et al, 2007, Yousuf et al, 2017, Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The altered photosynthetic phenotype likely resulted from adjusted enzyme concentrations in soybean leaves grown under ambient and elevated CO 2 concentrations. Such CO 2 -induced changes in protein concentrations was shown for total protein concentration in barley, rice, wheat, soybean, and potato (Taub et al, 2007) and for specific proteins via proteomic analysis in rice (Bokhari et al, 2007), wheat (Yousuf et al, 2017), and grape (Zhao et al, 2019). A decrease in the quantity of Rubisco is a pervading feature of plants grown in the field under elevated [CO 2 ] (Ainsworth and Long, 2005).…”
Section: Multiscale Model Developmentmentioning
confidence: 95%
“…Identification of the protein was carried out by searching the acquired mass spectrometer data in Swissprot (a non-redundant protein sequence database) using the MASCOT search engine version 3.5 (Matrix Science, UK). All the parameters for the identification of proteins were set according to Yousuf et al [60]. The functional categorization of proteins was analyzed with websites, including UniProt ().…”
Section: Methodsmentioning
confidence: 99%
“…GS assimilates ammonia and glutamate to form glutamine, and ferredoxin-dependent GOGAT catalyzes the synthesis of glutamate from glutamine and 2-oxoglutarate through transamidation reactions. In wheat, low N induces the activities of both enzymes in roots and leaves, not only to promote ammonia assimilation but also to achieve osmotic homeostasis via glutamate-based synthesis of proline (Kichey et al, 2005;Yousuf et al, 2017;Lv et al, 2021). TaNADH-GOGAT and its interaction with TabZIP60 play important roles in mediating N use and wheat growth (Yang et al, 2019a).…”
Section: N Assimilationmentioning
confidence: 99%